Pulmonary MRI contrast using Surface Quadrupolar Relaxation (SQUARE) of hyperpolarized 83Kr - Six, Joseph S.; Hughes-Riley, Theodore; Lilburn, David M.L.; Dorkes, Alan C.; Stupic, Karl F.; Shaw, Dominick E.; Morris, Peter G.; Hall, Ian P.; Pavlovskaya, Galina E.; Meersmann, Thomas (Elsevier, 2014)
Hyperpolarized 83Kr has previously been demonstrated to enable MRI contrast that is sensitive to the chemical composition of the surface in a porous model system. Methodological advances have lead to a substantial increase in the 83Kr hyperpolarization and the resulting signal intensity. Using the improved methodology for spin exchange optical pumping of isotopically enriched 83Kr, internal anatomical details of ex vivo rodent lung were resolved with hyperpolarized 83Kr MRI after krypton inhalation. Different 83Kr relaxation times were found between the main bronchi and the parenchymal regions in ex vivo rat lungs. The T1 weighted hyperpolarized 83Kr MRI provided a first demonstration of surface quadrupolar relaxation (SQUARE) pulmonary MRI contrast.